She didn't see it coming - Lapena, Shari, 1960- (Pamela Dorman Books/Viking, 2025)
"When a beloved wife and mother disappears, a luxurious condo building transforms into a potential crime scene, and the investigation begins: can the detectives find her before it's too late? Bryden and Sam have it all: thriving careers, a smart apartment in a luxury condominium, supportive friends and a cherished daughter. The perfect life for the perfect couple. Then Sam receives a call at his office. Bryden -- working from home that day -- has failed to collect their daughter from daycare. Arriving home with their little girl, he finds his wife's car in the underground garage. Upstairs in their apartment her laptop is open on the table, her cell phone nearby, her keys in their usual place in the hall. Except Bryden is nowhere to be seen. It's as if she just walked out. How can she have disappeared from her own home? And did she even leave the building at all? With every minute that passes -- and as questions swirl around their community -- Bryden and Sam's past seems a little less perfect, their condominium less safe, their friends, neighbors and relatives no longer quite so reliable ... "--